Zero-dimensional hybrid indium-based halide material with excellent photoluminescence property and preparation method and application thereof
The zero-dimensional hybrid indium-based halide material prepared by the solvothermal reaction method solves the problems of low luminescence efficiency and quantum yield of existing materials, achieves efficient and stable photoluminescence performance, and expands its application prospects in luminescent inks and white LEDs.
Patent Information
- Application Number
- CN202411575714.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-21
AI Technical Summary
The existing zero-dimensional indium-based halide materials have low luminescence efficiency and quantum yield, which limits their application in high-efficiency light emitting devices.
New zero-dimensional hybrid indium-based halide materials, including compounds A, B and C, were prepared by a solvothermal reaction method based on discrete [InBr6]3- and [InBr4(H2O)2]-octahedrons, including compounds A, B and C, using different combinations of organic amines and solvents to optimize the structure and properties of the material.
The quantum yield of these zero-dimensional hybrid indium-based halide materials is achieved close to 100%, greatly improving the emission efficiency and stability, and is suitable for applications such as luminescent inks and white light-emitting diodes.
Smart Images

Figure CN119661375A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of luminescent materials, and in particular to a zero-dimensional hybrid indium-based halide material with excellent photoluminescent properties, and a preparation method and application thereof. Background Art
[0002] Green, efficient and stable luminescent inks play an important role in various advanced optoelectronic fields and civilian life, including wearable smart devices, erasable luminescent paper and fluorescent anti-counterfeiting. In particular, inkjet-printed luminescent labels have excellent anti-counterfeiting properties, can prevent the leakage of confidential information, and have broad application prospects in the economic and military fields as well as our personal daily lives. At present, various soluble luminescent materials, including carbon dots, metal organic complexes, organic dyes and rare earth ion-doped phosphors, have been used to prepare luminescent inks. However, most inks still have various disadvantages such as cumbersome synthesis process, difficulty in large-scale preparation, high cost, environmental pollution problems and low quantum yield (PLQY), which seriously limit the application prospects of luminescent inks. Therefore, it is challenging and of great research significance to develop green, environmentally friendly, cost-effective and highly stable luminescent materials for the preparation of luminescent inks.
[0003] In recent years, zero-dimensional organic-inorganic hybrid metal halides have become a new generation of luminescent materials. This material can be considered as a derivative of three-dimensional halide perovskites obtained by regulating the structural dimension and composition. In zero-dimensional metal halides, inorganic anions and organic cations form an alternating, long-range ordered periodic structure through weak hydrogen bonds and electrostatic interactions. Due to the large difference in the band gap and dielectric constant between the inorganic and organic components, the metal halide anion units are divided and surrounded by organic cations to form a strong quantum confinement effect, which makes it easy for electrons to be localized on the isolated anion skeleton, so that the material has a high exciton binding energy and high luminescence efficiency. At the same time, due to the weak ionic bonds and low formation energy of zero-dimensional metal halides, the material can be prepared by low-temperature solution method or even solvent-free mechanical grinding method. In addition, the luminescence intensity of zero-dimensional metal halides is not affected by the size of the crystal, thus avoiding the aggregation quenching effect, and still has efficient and stable emission in the single crystal state. At the same time, the soft lattice of zero-dimensional metal halides has a high structural deformation ability, which leads to strong phonon vibration of the material under light excitation. Therefore, high-energy excitons are easily captured by phonons to form low-energy self-trapped excitons (STEs), which return to the ground state through radiative transitions to form low-energy luminescence. Therefore, zero-dimensional metal halides tend to form broadband light emission with large Stokes shift and high optical stability, which has important application value in the field of luminescent inks.
[0004] So far, a large number of main group and transition metal ions have been used to prepare zero-dimensional metal halides, including Zn2+ 、Cd 2+ , Mn 2+ , Cu + Sn 2+ , Pb 2+ 、In 3+ , Sb 3+ 、Te 4+ 、Zr 4+ Due to the rich structure-directing effect of organic cations, zero-dimensional metal halides show highly tunable chemical composition, crystal structure and luminescence properties. However, Cu + Sn 2+ The base halides have low stability, Cd 2+ and Pb 2+ The toxicity of Zn halides is relatively high. 2+ , Sb 3+ The emission color of the base halide phase is almost unchanged, Te 4+ and Zr 4+ Based halides have low PLQY. Compared with the above metal halides, indium-based halides have many unique advantages, such as low toxicity, high stability and oxidation resistance, tunable emission color, etc. These advantages make zero-dimensional indium-based halides one of the indispensable members of metal halide-based luminescent materials. However, the application of most zero-dimensional indium-based halides is restricted by low luminescence efficiency and low quantum yield (<50%), making it difficult to develop them into efficient light-emitting devices. Therefore, it is of great research significance to explore efficient and stable zero-dimensional indium-based halide luminescent materials at the molecular level through crystal engineering strategies. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a zero-dimensional hybrid indium-based halide material with excellent photoluminescent properties, which has high quantum yield, ultra-high emission efficiency, stability and excellent performance in various luminescent fields. The present invention also provides a preparation method thereof and the application of the above indium-based halide material in luminescent ink and white light emitting diodes.
[0006] The method for preparing the zero-dimensional hybrid indium-based halogenated material with excellent photoluminescence performance of the present invention comprises the following steps:
[0007] (1) dissolving anhydrous indium acetate in a mixed solvent of a hydrohalic acid and an organic solvent, then adding an organic amine, stirring thoroughly until dissolved to obtain a mixed solution, and placing the solution into a reaction container;
[0008] (2) sealing the reaction container, subjecting the mixed solution to a hydrothermal reaction, and naturally cooling to room temperature after the reaction, standing, washing, and drying to obtain the zero-dimensional hybrid indium-based halide;
[0009] Wherein, in step (1), the hydrohalic acid is hydrobromic acid; when the organic amine is di-n-propylamine, the organic solvent is ethanol and isobutyl alcohol, and the obtained zero-dimensional hybrid indium halide is recorded as compound A; when the organic amine is N,N'-di-tert-butylethylenediamine, the organic solvent is n-propanol, and the obtained zero-dimensional hybrid indium halide is recorded as compound B; when the organic amine is N-aminopropylmorpholine, the organic solvent is acetone and isopropyl alcohol, and the obtained zero-dimensional hybrid indium halide is recorded as compound C.
[0010] Preferably, when the organic solvent is ethanol and isobutanol, the volume ratio of the hydrohalic acid, ethanol and isobutanol is 1:(1-2):(9-10), and the volume ratio of the mixed solvent to anhydrous indium acetate is (4-6):1;
[0011] When the volume ratio of the organic solvent n-propanol, the hydrohalic acid and n-butanol is 1:(10-15), the volume ratio of the mixed solvent and anhydrous indium acetate is (4-6):1;
[0012] When the organic solvent is acetone and isopropanol, the volume ratio of the hydrohalic acid, acetone and isopropanol is 1:1:(2-4), and the volume ratio of the mixed solvent to anhydrous indium acetate is (3-5):1.
[0013] Preferably, in step (2), the reaction temperature is 80-100° C., the reaction time is 5-7 days, and the reaction is allowed to stand for 15-30 days.
[0014] Preferably, the molar ratio of the organic amine to anhydrous indium acetate is 1:(2-3).
[0015] The preparation method of the invention provides a zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance.
[0016] Preferably, the molecular formula of compound A is [DPA] 3 InBr 6 , the crystal space group is R-3c, the unit cell parameters α=β=90°,γ=120°,the unit cell volume is
[0017]
[0018] The molecular formula of compound B is [D(t-Bu)EDA] 2 (InBr 6 )(InBr 4 (H 2 O) 2 ), the crystal system space group is P-1, the unit cell parameters α=97.096(4)°,β=95.642(4)°,γ=110.318(4)°,the unit cell volume is
[0019] The molecular formula of compound C is [4-APrMor] 2 (InBr 6 )(InBr 4 (H 2 O) 2 )·2H 2 O, crystal system space group is P-1, unit cell parameters α=79.426(2)°,β=85.706(2)°,γ=63.357(2)°,the unit cell volume is
[0020] The invention discloses an application of the zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance in luminescent ink.
[0021] The method for preparing the above-mentioned luminescent ink comprises the following steps:
[0022] The zero-dimensional hybrid indium-based halide is mixed and stirred with polyvinyl pyrrolidone (PVP) to obtain composite microcrystals; the composite microcrystals are dispersed in tert-butyl alcohol to form a transparent solution.
[0023] The invention discloses an application of the zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance in white light emitting diodes (LEDs).
[0024] The above-mentioned method for preparing a white light emitting diode comprises the following steps:
[0025] The zero-dimensional hybrid indium-based halide and BaMgAl 10 O 17 :Eu 2+ The blue phosphor is mixed to obtain a mixture, and the mixture is coated on a 365nm UV LED chip to obtain.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention adopts a simple solvent thermal reaction method based on discrete [InBr 6 ] 3- and [InBr 4 (H 2 O) 2 ] - Octahedral preparation of zero-dimensional hybrid indium-based halide materials, namely three new zero-dimensional hybrid indium-based halide materials [DPA] 3 InBr 6 , [D(t-Bu)EDA] 2 (InBr 6 )(InBr 4 (H 2 O) 2) and [4-APrMor] 2 (InBr 6 )(InBr 4 (H 2 O) 2 )·2H 2 O; highly dispersed and distorted [InBr 6 ] 3- and [InBr 4 (H 2 O) 2 ] - The octahedron makes the PLQY of these zero-dimensional hybrid indium-based halide materials close to 100%, which greatly breaks through the existing technical level; based on this, the oily luminescent ink obtained by the present invention still shows the same strong emission light in most organic solvents, and can be used to print anti-counterfeiting patterns on various substrates;
[0028] The efficient broadband yellow light emission of the present invention also shows potential application in solid-state white light emitting diodes, with a color rendering index (CRI) of more than 90, which is better than commercially available white light LEDs;
[0029] In summary, the zero-dimensional hybrid indium-based halide prepared by the present invention demonstrates a variety of optoelectronic applications in luminescent inks and white light-emitting diodes, and its ultra-high emission efficiency, stability and excellent performance in various luminescent fields expand the application prospects of zero-dimensional hybrid indium-based halide materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagrams of the crystal structures of compounds A, B, and C obtained in Examples 1-3 of the present invention, wherein (a) is a schematic diagram of the zero-dimensional structure of compound A, (b) is a schematic diagram of the zero-dimensional structure of compound B, and (c) is a schematic diagram of the zero-dimensional structure of compound C.
[0031] Figure 2 The powder X-ray diffraction patterns of compounds A, B and C prepared in Examples 1-3 of the present invention.
[0032] Figure 3 Solid-state UV-visible absorption spectra of compounds A, B, and C prepared in Examples 1-3 of the present invention, wherein (a) is a solid-state UV-visible absorption spectrum band gap diagram of compound A, (b) is a solid-state UV-visible absorption spectrum band gap diagram of compound B, and (c) is a solid-state UV-visible absorption spectrum band gap diagram of compound C.
[0033] Figure 4 The excitation spectra and emission spectra of the crystals of compounds A, B, and C prepared in Examples 1-3 of the present invention at 300K, wherein (a) is the excitation spectrum and emission spectrum of compound A, (b) is the excitation spectrum and emission spectrum of compound B, and (c) is the excitation spectrum and emission spectrum of compound C.
[0034] Figure 5 It is the quantum yield of compounds A, B and C prepared in Examples 1-3 of the present invention under ultraviolet light excitation.
[0035] Figure 6 The power-dependent emission spectra of compounds A, B, and C prepared in Examples 1-3 of the present invention at 300K.
[0036] Figure 7 X-ray diffraction patterns of compounds A, B and C obtained in Examples 1-3 of the present invention continuously heated at a temperature of 300K-400K, wherein (a) is the X-ray diffraction pattern of compound A continuously heated at a temperature of 300K-400K, (b) is the X-ray diffraction pattern of compound B continuously heated at a temperature of 300K-400K, and (c) is the X-ray diffraction pattern of compound C continuously heated at a temperature of 300K-400K.
[0037] Figure 8 Comparative emission spectra of compounds A, B and C obtained in Examples 1-3 of the present invention under continuous heating at 300K-400K, wherein (a) is the PL emission spectrum of compound A at 300K-400K that varies with temperature, (b) is the PL emission spectrum of compound B at 300K-400K that varies with temperature, and (c) is the PL emission spectrum of compound C at 300K-400K that varies with temperature.
[0038] Fig. 9 The figures are comparison diagrams of the powder X-ray diffraction of compounds A, B and C prepared in Examples 1-3 of the present invention before and after being stored in humid air for one week, wherein (a) is the powder X-ray diffraction diagram of compound A, (b) is the powder X-ray diffraction diagram of compound B, and (c) is the powder X-ray diffraction diagram of compound C.
[0039] Fig.10 The emission spectra of compounds A, B, and C prepared in Examples 1-3 of the present invention before and after being stored in humid air for one week are compared, wherein (a) is the emission spectrum of compound A, (b) is the emission spectrum of compound B, and (c) is the emission spectrum of compound C.
[0040] Fig.11 The figures are comparison diagrams of the powder X-ray diffraction of compounds A, B and C prepared in Examples 1-3 of the present invention before and after being immersed in various organic solvents for one week, wherein (a) is the powder X-ray diffraction diagram of compound A, (b) is the powder X-ray diffraction diagram of compound B, and (c) is the powder X-ray diffraction diagram of compound C.
[0041] Fig.12The emission spectra of compounds A, B, and C prepared in Examples 1-3 of the present invention before and after being immersed in various organic solvents for one week are compared, wherein (a) is the emission spectrum of compound A, (b) is the emission spectrum of compound B, and (c) is the emission spectrum of compound C.
[0042] Fig.13 The figures are comparison diagrams of the powder X-ray diffraction of compounds A, B and C prepared in Examples 1-3 of the present invention before and after irradiation with natural light for 24 hours, wherein (a) is the powder X-ray diffraction diagram of compound A, (b) is the powder X-ray diffraction diagram of compound B, and (c) is the powder X-ray diffraction diagram of compound C.
[0043] Fig.14 The emission spectra of compounds A, B, and C prepared in Examples 1-3 of the present invention before and after irradiation with natural light for 24 hours are compared, wherein (a) is the emission spectrum of compound A, (b) is the emission spectrum of compound B, and (c) is the emission spectrum of compound C.
[0044] Fig.15 The emission spectra of the crystals and powders of compounds A, B, and C prepared in Examples 1-3 of the present invention are compared.
[0045] Fig.16 The temperature-dependent PL emission spectra of compounds A, B, and C prepared in Examples 1-3 of the present invention.
[0046] Fig.17 The fitting relationship between the emission intensity and the reciprocal temperature of compounds A, B, and C prepared in Examples 1-3 of the present invention.
[0047] Fig.18 The figure is the fitting relationship between the half-peak width and temperature of compounds A, B and C prepared in Examples 1-3 of the present invention.
[0048] Fig.19 The photographs (a) of the luminescent ink prepared by using the compound B / PVP composite microcrystals prepared in Example 2 of the present invention in tert-butanol under natural light and 365 nm ultraviolet light, and the printed pattern (b) on commercial paper.
[0049] Fig. 20 The quantum yield of the luminescent ink prepared by using the compound B / PVP composite microcrystals prepared in Example 2 of the present invention in tert-butanol under ultraviolet light excitation.
[0050] Fig.21 Schematic diagram of the manufacture of the white light LED of compound B prepared in Example 2 of the present invention (a), the electroluminescence (EL) emission spectrum at a driving current of 20 mA (b), color photographs under natural light and white light LED irradiation (c), the driving current-dependent EL emission spectrum (d), and the luminous efficiency diagram (e).
[0051] Fig. 22 EL emission spectrum of the white light LED of compound C prepared in Example 3 of the present invention at a driving current of 20 mA (a) and a graph of luminous efficiency related to the working time (b).
[0052] Fig.23 EL emission spectrum of the white light LED of compound A prepared in Example 1 of the present invention at a driving current of 20 mA (a) and a graph of luminous efficiency related to the working time (b). DETAILED DESCRIPTION
[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments.
[0054] The raw materials used in the embodiment are as follows:
[0055] Among them, anhydrous indium acetate (Merrill Reagent Company, 99.99%);
[0056] Di-n-propylamine (Aladdin Reagent Company, 99%);
[0057] N,N'-di-tert-butylethylenediamine (Aladdin Reagent Company, 98%);
[0058] N-aminopropylmorpholine (purity 98%);
[0059] Hydrobromic acid (McLean Reagent, 40%);
[0060] Ethanol (McLean Reagent, 99.7%);
[0061] Isobutanol (McLean Reagent, 98%);
[0062] n-Propanol (McLean Reagent Company, 99%);
[0063] Acetone (Aladdin Reagent Company, AR);
[0064] Isopropanol (McLean Reagent, 99.5%);
[0065] The reaction vessel is a 10 mL glass bottle that can withstand temperatures below 120°C.
[0066] Example 1
[0067] (1) dissolving 0.15 g of anhydrous indium acetate in a mixed solvent of hydrobromic acid, ethanol and isobutyl alcohol (volume ratio of 1:2:10), stirring thoroughly until dissolved, then adding di-n-propylamine to obtain a mixed solution, and adding the solution to a reaction container; wherein the volume ratio of anhydrous indium acetate to the mixed solvent is 1:6, and the molar ratio of di-n-butylamine to anhydrous indium acetate is 1:2;
[0068] (2) The sealed reaction vessel was placed in an electric heated blast drying oven with programmable temperature control to carry out a hydrothermal reaction at a temperature of 80° C. for 5 days. After the reaction was completed, the reaction vessel was naturally cooled to room temperature, allowed to stand for 15 days, and then washed and dried to obtain the target compound A.
[0069] Example 2
[0070] (1) dissolving 0.15 g of anhydrous indium acetate in a mixed solvent of hydrobromic acid and n-propanol (volume ratio of 1:10), stirring thoroughly until dissolved, then adding N,N'-di-tert-butylethylenediamine to obtain a mixed solution, and adding the solution to a reaction container; wherein the volume ratio of anhydrous indium acetate to the mixed solvent is 1:5, and the molar ratio of N,N'-di-tert-butylethylenediamine to anhydrous indium acetate is 1:2;
[0071] (2) The sealed reaction vessel was placed in an electric heated blast drying oven with programmable temperature control to carry out a hydrothermal reaction at a temperature of 80° C. for a reaction time of 5 days. After the reaction was completed, the reaction vessel was naturally cooled to room temperature, allowed to stand for 10 days, and then washed and dried to obtain the target compound B.
[0072] Example 3
[0073] (1) dissolving 0.1 g of anhydrous indium acetate in a mixed solvent of hydrobromic acid, acetone and isopropanol (volume ratio of 1:1:3), stirring thoroughly until dissolved, then adding N-aminopropylmorpholine to obtain a mixed solution, and adding the solution to a reaction container; wherein the volume ratio of anhydrous indium acetate to the mixed solvent is 1:4, and the molar ratio of N-aminopropylmorpholine to anhydrous indium acetate is 1:2;
[0074] (2) The sealed reaction vessel was placed in an electric heated blast drying oven with programmable temperature control to carry out a hydrothermal reaction at a temperature of 80° C. for 5 days. After the reaction was completed, the reaction vessel was naturally cooled to room temperature, allowed to stand for 10 days, and then washed and dried to obtain the target compound C.
[0075] Performance Testing
[0076] The instruments and detection methods used are as follows:
[0077] The electric heating blast drying oven was provided by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9240(A).
[0078] The crystal structure was determined by single crystal X-ray diffractometer (Bruker, Germany, APEX-IICCD).
[0079] The powder diffraction was measured by X-ray powder diffractometer (Bruker D8 ADVANCE), and the UV-visible absorption spectrum was measured by UV-visible spectrophotometer (PE Lambda 900).
[0080] PL spectroscopy was performed on an Edinburgh FLS980 fluorescence spectrometer.
[0081] The photoluminescence quantum yield was achieved by adding an integrating sphere to the FLS1000 fluorescence spectrometer.
[0082] The white light LED test was carried out on the Yuanfang LED300E programmable LED test power supply and the HAAS-2000 high-precision fast spectroradiometer.
[0083] The molecular formula of the compound A finally prepared is [DPA] 3 InBr 6 (DPA = dipropylamine), the crystal space group is R-3c, α=β=90°,γ=120°,the unit cell volume is
[0084] The molecular formula of compound B is [D(t-Bu)EDA] 2 (InBr 6 )(InBr 4 (H 2 O) 2 ), the crystal system space group is P-1, the unit cell parameters α=97.096(4)°,β=95.642(4)°,γ=110.318(4)°,the unit cell volume is
[0085] The molecular formula of compound C is [4-APrMor] 2 (InBr 6 )(InBr 4 (H 2 O) 2 )·2H 2 O, crystal system space group is P-1, unit cell parameters α=79.426(2)°,β=85.706(2)°,γ=63.357(2)°,the unit cell volume is
[0086] Figure 1 Schematic diagram of the crystal structure of compound A, compound B and compound C. Figure 1 As shown in (a), single crystal X-ray diffraction shows that the crystal structure of compound A consists of discrete [InBr 6 ] 3- Octahedron, composed of [DPA] + The cations balance the charge. All indium ions are coordinated by six bromide ions in a slightly distorted [InBr 6 ] octahedron. [InBr 6] 3- Octahedron surrounded [DPA] + The cations are isolated to form a typical zero-dimensional structure. Figure 1 As shown in (b) and (c), single crystal X-ray diffraction shows that the crystal structures of compound B and compound C are composed of discrete [InBr 6 ] 3- and [InBr 4 (H 2 O) 2 ] - Octahedral composition, composed of [D(t-Bu)EDA] 2+ and [4-APrMor] 2+ Cationic charge balance. All indium ions are coordinated by six bromide ions or four bromide ions and two water molecules, [InBr 4 (H 2 O) 2 ]The deformation level of the octahedron is large. The adjacent [InBr 6 ] and [InBr 4 (H 2 O) 2 ] octahedral layers, they are [D(t-Bu)EDA] 2+ or [4-APrMor] 2+ The cations separate to form a long-range ordered zero-dimensional structure.
[0087] like Figure 2 As shown, the powder diffraction patterns of compound A, compound B and compound C are consistent with the data of single crystal structure simulation, indicating that the purity of compound A, compound B and compound C is close to the theoretical value (100%).
[0088] like Figure 3 As shown, the band gaps of Compound A, Compound B and Compound C are determined to be 3.027 eV, 2.679 eV and 2.637 eV respectively by dividing the relative energy (1240 nm / eV) by the maximum emission wavelength. It should be noted that the weak broadband absorption tail below the cutoff wavelength comes from the electronic transition in the corresponding organic component.
[0089] like Figure 4 As shown, under UV excitation, compounds A, B, and C exhibit broadband light emission in almost the entire visible light range, with maximum peaks at 545 nm, 558 nm, and 601 nm, respectively. These broadband light emissions are manifested by wide half-peak widths of 111 nm, 127 nm, and 127 nm, and large Stokes shifts of 180 nm, 194 nm, and 228 nm.
[0090] In order to verify the commercial application prospects of these halides in the field of LEDs, the present invention tests the quantum yields of these zero-dimensional halides under ultraviolet light excitation.
[0091] like Figure 5 As shown in the figure, the quantum yields of the three compounds under UV excitation are 84.39%, 98.26% and 71.69%, respectively. It is worth noting that the highest quantum yield of compound B has exceeded all reported mixed indium halides. For example, (C 13 H 14 N 3 ) 3 InBr(86.12%), [H 2 DMP] 2 InCl 7 ·2H 2 O (58.53%), [DADPA]InCl 6 ·H 2 O (41.27%), [DAPEDA]InCl 6 ·Cl·H 2 O(40.40%), (PMA) 3 InBr 6 (35.00%).
[0092] In addition to their striking photoluminescent properties, these zero-dimensional halides also possess sufficient structural and luminescent stability at least above 400 K.
[0093] like Figure 7 and Figure 8 As shown, compounds A, B, and C were continuously heated at 300K-400K, and the PXRD patterns and PL emission spectra did not change significantly.
[0094] In addition, compounds A, B, and C also have sufficient structural and luminescence stability under humid air, various organic solvents, and natural light.
[0095] like Figures 9 to 14 As shown, the PXRD patterns and PL emission spectra of compounds A, B, and C did not change significantly when exposed to humid air, various organic solvents, and natural light, respectively.
[0096] To confirm the nature of broadband light emission, the present invention further compared the emission spectra of bulk crystals and micron-sized powders of all phases.
[0097] like Fig.15As shown, the almost identical photoluminescence emission curves and intensities of compounds A, B, and C exclude the possibility of crystal defect-induced emission, which is further supported by the linear relationship between emission intensity and excitation power density. Therefore, these broadband light emissions can be tentatively attributed to the radiative recombination of triplet self-trapped exciton emission.
[0098] To confirm this inference, temperature-dependent PL emission spectroscopy from 300 K to 80 K was performed.
[0099] like Fig.16 As shown, compounds A, B, and C have only one emission peak in the entire temperature range without any splitting, indicating that the emission should come from the same excited state in all phases. As the temperature decreases, the highest emission peak of compound A has almost no displacement, while the highest emission peaks of compound B and compound C are slightly blue-shifted from 558nm and 601nm to 552nm and 595nm, respectively. During the cooling process, the weakened thermally induced non-radiative recombination rate leads to a monotonous increase in the emission intensity. According to the Arrhenius equation, the relevant thermal activation energy (Ea) can be extracted from the temperature-dependent emission intensity. As shown in Fig.17 As shown, for compounds A, B, and C, the evaluated Ea values are 41.00meV, 42.33meV, and 54.39meV, which are significantly higher than the thermal dissociation energy of excitons at 300K (~26meV). The higher energy barrier ensures the formation of stable excitons to overcome thermal decomposition and subsequently produce strong luminescence at room temperature. At the same time, due to the enhanced coupling between electrons and acoustic phonons, the PL emission spectrum width (FWHM) gradually widens with increasing temperature, further strongly confirming the nature of self-trapped exciton emission. Here, the electron-phonon coupling strength can be evaluated by the Huang Kun factor. The Huang Kun factor and the phonon frequency can be obtained by fitting the temperature-dependent FWHM, as shown in Fig.18 As shown in Figure 2, the estimated Huang-Kun factors of compounds A, B, and C are 28.08, 17.47, and 15.21, respectively, which are much larger than typical narrow-band emission luminescent materials such as 3D CsPbX 3 (1.5-3.3), etc., illustrating the softer organic-inorganic hybrid lattice and stronger electron-phonon coupling.
[0100] In order to explore the potential application of compound B in luminescent ink and white light emitting diodes, the present invention has made the following explorations:
[0101] The zero-dimensional hybrid indium-based halide obtained in Example 2, namely compound B, and polyvinyl pyrrolidone were mixed and stirred at a mass ratio of 1:1 to obtain composite microcrystals; the composite microcrystals were dispersed in tert-butyl alcohol to form a transparent solution to obtain luminescent ink, wherein the molar volume ratio of polyvinyl pyrrolidone to tert-butyl alcohol was 1 mol:100 mL.
[0102] like Fig.19As shown in (a), compound B / PVP composite microcrystals are dispersed in tert-butyl alcohol to form a transparent solution, in which PVP plays a vital role in stabilizing the halide particles to avoid deposition. Fig. 20 As shown in Figure 2, the solution emits bright yellow light under ultraviolet light, with a PLQY as high as 58.51%, and can be used as fluorescent ink for laser inkjet or screen printing technology. Fig.19 As shown in (b), a series of anti-counterfeiting patterns, such as the moon, flowers, QR codes, and Chinese characters, were printed on commercial paper. As the organic solvent evaporates during the drying process, the microcrystals of compound B are deposited on the paper surface in the designed pattern again. Compared with its invisibility under sunlight, the printed patterns appear yellow with high spatial resolution under 365nm UV light. In addition, these printed models still emit bright yellow light after being stored in the environment for 1 month, showing ultra-high stability. The contrast between invisible light and visible light under alternating irradiation of visible light and UV light provides a controllable photoreversible switch for anti-counterfeiting applications.
[0103] The high efficiency and stability of broadband yellow light emission further inspired us to explore the potential application of solid-state white light LEDs. In order to verify the application in solid-state lighting, the zero-dimensional hybrid indium-based halides obtained in Examples 1-3, namely compounds A, B, and C, were used as yellow phosphors and commercial BaMgAl 10 O 17 :Eu 2+ As a mixture of blue phosphors coated on a 365nmUV chip.
[0104] The detailed assembly process is as follows: Fig.21 (a). Fig.21 As shown in (b), the white light LED based on compound B emits bright white light when driven by a current of 20 mA, and the corresponding electroluminescence (EL) emission spectrum provides a wide dual-band covering the entire visible light region, with a color rendering index (CRI) as high as 90.7, a correlated color temperature (CCT) of 5162 K, and a CIE coordinate of (0.34, 0.33). White light LEDs based on compounds A and C also exhibit high CRIs of 90 and 88.4 ( Fig. 22 (a) and 23(a)). The color rendering index is higher than that based on YAG:Ce 3+ (CRI < 80) commercially available white LEDs with yellow phosphor. The color images show the same brightness under sunlight and the manufactured white LEDs, indicating the high quality performance of the white LEDs ( Fig.21 (c)). As the driving current increases from 20mA to 120mA, the EL emission intensities of the dual emission bands increase respectively, and there is no energy transfer and reabsorption between the two phosphors, which indicates its potential application in high-power lighting devices ( Fig.21(d) and 21(e)). Moreover, during constant operation for several hours, the luminous efficiency related to the operating time remained almost constant, demonstrating the high color stability ( Fig. 22 (b) and 23(b)). Therefore, these zero-dimensional hybrid indium-based halides can be used as promising down-conversion yellow phosphors to fabricate white light-emitting LEDs with excellent luminescence performance and stability.
Claims
1. A method for preparing a zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance, characterized in that: The following steps are involved: (1) dissolving anhydrous indium acetate in a mixed solvent of a hydrohalic acid and an organic solvent, then adding an organic amine, stirring until dissolved to obtain a mixed solution, and placing the mixed solution in a reaction container; (2) sealing the reaction container, subjecting the mixed solution to a hydrothermal reaction, and naturally cooling to room temperature after the reaction, standing, washing, and drying to obtain the zero-dimensional hybrid indium-based halide; Wherein, in step (1), the hydrohalic acid is hydrobromic acid; when the organic amine is di-n-propylamine, the organic solvent is ethanol and isobutyl alcohol, and the obtained zero-dimensional hybrid indium halide is recorded as compound A; when the organic amine is N,N'-di-tert-butylethylenediamine, the organic solvent is n-propanol, and the obtained zero-dimensional hybrid indium halide is recorded as compound B; when the organic amine is N-aminopropylmorpholine, the organic solvent is acetone and isopropyl alcohol, and the obtained zero-dimensional hybrid indium halide is recorded as compound C.
2. The method for preparing a zero-dimensional hybrid indium-based halide material having excellent photoluminescence performance according to claim 1, characterized in that: When the organic solvent is ethanol and isobutanol, the volume ratio of the hydrohalic acid, ethanol and isobutanol is 1:(1-2):(9-10), and the volume ratio of the mixed solvent to anhydrous indium acetate is (4-6):1; When the volume ratio of the organic solvent n-propanol, the hydrohalic acid and n-butanol is 1:(10-15), the volume ratio of the mixed solvent and anhydrous indium acetate is (4-6):1; When the organic solvent is acetone and isopropanol, the volume ratio of the hydrohalic acid, acetone and isopropanol is 1:1:(2-4), and the volume ratio of the mixed solvent to anhydrous indium acetate is (3-5):
1.
3. The method for preparing the zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance according to claim 1, characterized in that: In step (2), the reaction temperature is 80-100° C., the reaction time is 5-7 days, and the reaction is allowed to stand for 15-30 days.
4. The method for preparing a zero-dimensional hybrid indium-based halide material having excellent photoluminescence performance according to claim 1, characterized in that: The molar ratio of the organic amine to anhydrous indium acetate is 1:(2-3).
5. A zero-dimensional hybrid indium-based halide material having excellent photoluminescence performance obtained by the preparation method according to any one of claims 1 to 4.
6. The zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance according to claim 5, characterized in that: The molecular formula of compound A is [DPA]3InBr6, the crystal space group is R-3c, and the unit cell parameters are α=β=90°,γ=120°,the unit cell volume is The molecular formula of compound B is [D(t-Bu)EDA]2(InBr6)(InBr4(H2O)2), the crystal space group is P-1, and the unit cell parameters are α=97.096(4)°,β=95.642(4)°,γ=110.318(4)°,the unit cell volume is The molecular formula of compound C is [4-APrMor]2(InBr6)(InBr4(H2O)2)·2H2O, the crystal space group is P-1, and the unit cell parameters are α=79.426(2)°,β=85.706(2)°,γ=63.357(2)°,the unit cell volume is 7. Use of the zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance as claimed in claim 6 in luminescent ink.
8. Use of the zero-dimensional hybrid indium-based halide material with excellent photoluminescence performance as claimed in claim 6 in white light emitting diodes.